Cryopreservation of mesenchymal stem cells derived from dental pulp: a systematic review - Sabrina Moreira Paes; Yasmine Mendes Pupo; Bruno Cavalini Cavenago; Thiago Fonseca-Silva; Carolina Carvalho de Oliveira Santos (Restorative Dentistry & Endodontics)
ObjectivesThe aim of the present systematic review was to investigate the cryopreservation process of dental pulp mesenchymal stromal cells and whether cryopreservation is effective in promoting cell viability and recovery.Materials and MethodsThis systematic review was developed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and the research question was determined using the population, exposure, comparison, and outcomes strategy. Electronic searches were conducted in the PubMed, Cochrane Library, Science Direct, LILACS, and SciELO databases and in the gray literature (dissertations and thesis databases and Google Scholar) for relevant articles published up to March 2019. Clinical trial studies performed with dental pulp of human permanent or primary teeth, containing concrete information regarding the cryopreservation stages, and with cryopreservation performed for a period of at least 1 week were included in this study.ResultsThe search strategy resulted in the retrieval of 185 publications. After the application of the eligibility criteria, 21 articles were selected for a qualitative analysis.ConclusionsThe cryopreservation process must be carried out in 6 stages: tooth disinfection, pulp extraction, cell isolation, cell proliferation, cryopreservation, and thawing. In addition, it can be inferred that the use of dimethyl sulfoxide, programmable freezing, and storage in liquid nitrogen are associated with a high rate of cell viability after thawing and a high rate of cell proliferation in both primary and permanent teeth.